Short-term surgical outcomes of preterm infants with necrotizing enterocolitis: A single-center experience. Issue 30 (July 2016) - Sheng, Qingfeng; Lv, Zhibao; Xu, Weijue; Liu, Jiangbin; Wu, Yibo; Shi, Jingyi; Xi, Zhengjun
Abstract : Abstract: The purpose of this study was to analyze the nature of the disease, the surgical procedures, complications, and survival of preterm infants with necrotizing enterocolitis (NEC) at our institution. Medical records of 34 preterm (gestational age <37 weeks) infants with surgical NEC were retrospectively analyzed from January 2010 to December 2014. Patients were divided into 2 groups: low birth weight (LBW, <2500 g, n = 27) and normal birth weight (NBW, ≥2500 g, n = 7). The LBW and NBW groups differed dramatically in gestational age (31.2 ± 2.2 vs. 36.3 ± 0.5 weeks), and respiratory support (55.5% vs. 0%). The median age of NEC onset was 12 and 5 postnatal days respectively. There was an inverse association between gestational age and day of NEC onset (r = −0.470). Pneumoperitoneum, positive paracentesis, and progressive clinical deterioration were the indications for laparotomy. There was no difference in the extent of disease, in the bowel involvement, in the surgical procedures, and in the postoperative complication rates between the 2 groups. The choice of procedure has often depended upon the extent of disease (enterostomy was performed in most localized and multifocal infants, simple drainage was used in 83.3% pan-intestinal patients, P  < 0.001). Postoperative complications occurred in 70.5% patients. The most common complications were sepsis, intestinal stricture, and short bowel syndrome. The median hospital stay was significantly longer in the LBW group (65 vs. 19 days, P  = 0.004). The overall postoperative 180-day survival rate was 70.6% (70.4% vs. 71.5%, P  = 0.890, log rank test). The severity of illness was the main risk factor for mortality (8.3% in localized, 18.7% in multifocal, and 100% in pan-intestinal, P  < 0.001). The short-term outcomes for surgical NEC are grave. The high mortality and postoperative complications in this study mandate urgent improvements in early recognition, expeditious operation, and better perioperative care.